2016
DOI: 10.4049/jimmunol.1502112
|View full text |Cite
|
Sign up to set email alerts
|

Kras Is Critical for B Cell Lymphopoiesis

Abstract: The three major Ras members, Kras, Hras and Nras, are highly homologous and individual Ras gene can have distinct biological functions. Embryonic lethality of Kras-deficient mice precludes study of the biological functions of this Ras family member. Here, we generated and examined mice with hematopoietic-specific deletion of Kras and bone marrow (BM) chimeric mice with B cell-specific targeted deletion of Kras. Hematopoietic-specific deletion of Kras impaired early B cell development at the pre-B-cell stage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…S7). Consistent with our finding, recent work from Chen and colleagues showed that the ERK1/2 pathway is downregulated in Kras 2/2 B cells, which is associated with B cell differentiation defects at both pre-B cell and mature B cell stages [41]. Together, these data indicate loss of Kras leads to various defects in differentiated hematopoietic cells, which could contribute to reduced reconstitution of Kras 2/2 -derived cells in recipients.…”
Section: Discussionsupporting
confidence: 92%
“…S7). Consistent with our finding, recent work from Chen and colleagues showed that the ERK1/2 pathway is downregulated in Kras 2/2 B cells, which is associated with B cell differentiation defects at both pre-B cell and mature B cell stages [41]. Together, these data indicate loss of Kras leads to various defects in differentiated hematopoietic cells, which could contribute to reduced reconstitution of Kras 2/2 -derived cells in recipients.…”
Section: Discussionsupporting
confidence: 92%
“…This could contribute to the enhanced constitutive activation of the p-Akt/p-S6 pathway in IgH.TE Îź CLL as reported previously ( 23 , 24 ). Additionally, genes involved in KRAS signaling were highly expressed in both CLL subsets, consistent with its essential role in B cell lymphopoesis ( 60 ), particularly for B-1 cells recognizing PtC ( 61 ).…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, the ERK1/2 pathway is down-regulated in Kras ÂĄ/ÂĄ B cells, which is associated with B cell differentiation defects at both pre-B cell and mature B cell stages. 10 These results reveal a surprising, indispensible role of Kras in mediating cell typeand cykokine-specific ERK1/2 activation, especially in differentiated cells (e.g. neutrophils).…”
mentioning
confidence: 87%